2009
DOI: 10.1007/s10750-009-9911-9
|View full text |Cite
|
Sign up to set email alerts
|

Diving beetle assemblages of flooded wetlands in relation to time, wetland type and Bti-based mosquito control

Abstract: This paper has not been submitted elsewhere in identical or similar form, nor will it be during the first three months after its submission to Hydrobiologia. 2 AbstractWe investigated the abundance and taxonomic composition of the aquatic predatory insect fauna, with focus on adult diving beetles (Coleoptera: Dytiscidae), in eight temporary flooded relation to time and wetland type, and 2) to evaluate the effect on the aquatic predator assemblage of strongly reducing the abundance of a potential prey, flood-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This is due in part to the importance this group in aquatic environments, both in abundance and diversity (Gray, 1981;Ramirez and Pringle, 1998;Stenert et al, 2004;Tupinambas et al, 2007;Paula and Fonseca-Gessner, 2010), as well as in the dynamics of aquatic systems, as part of the energy flow and nutrient dynamics (Larson, 1997;Peterson et al, 1999;Casatti et al, 2009;Vinnersten et al, 2009;Cobbaert et al, 2010). In recent years, water beetles have been gaining attention in monitoring programmes and environmental assessments, due to the sensitivity of some families to environmental change (Hilsenhoff, 1977;Ribera and Foster, 1992;Ribera, 2000;Garcia-Criado and Fernandez-Aláez, 2001;Compen and Céréghino, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the importance this group in aquatic environments, both in abundance and diversity (Gray, 1981;Ramirez and Pringle, 1998;Stenert et al, 2004;Tupinambas et al, 2007;Paula and Fonseca-Gessner, 2010), as well as in the dynamics of aquatic systems, as part of the energy flow and nutrient dynamics (Larson, 1997;Peterson et al, 1999;Casatti et al, 2009;Vinnersten et al, 2009;Cobbaert et al, 2010). In recent years, water beetles have been gaining attention in monitoring programmes and environmental assessments, due to the sensitivity of some families to environmental change (Hilsenhoff, 1977;Ribera and Foster, 1992;Ribera, 2000;Garcia-Criado and Fernandez-Aláez, 2001;Compen and Céréghino, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests and field studies have shown that Bti may be considered as safe to the environment due to its selectivity (Mulla et al 1982;Barnes and Chapman 1998;Boisvert and Lacoursière 2004). However, larvae of some species of non-target Nematocera (Chironomidae) have been shown to be susceptible to Bti (Kondo et al 1992;Rey et al 1998), and results of in situ studies on the impact of Bti-containing larvicides on non-target organisms remain controversial (Hershey et al 1995(Hershey et al , 1998Liber et al 1998;Niemi et al 1999;Vinnersten et al 2009). Spinosad is a new biological insecticide that is currently evaluated as a candidate larvicide for mosquito control.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers touch on the problem of how environmental factors influence the characteristics of beetle groups found in the various water ecosystems located within the floodplains of rivers (Persson Vinnersten et al, 2009;Pakulnicka and Nowakowski, 2012;Costea et al, 2013). However, only factors of local significance to the water environment had been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a deficit of detailed studies presenting a more in-depth analysis of dependencies between the beetle fauna of various waters related hydrologically, particularly between the fauna of rivers and valley water bodies (Biesiadka and Pakulnicka, 2004a;Pakulnicka and Nowakowski, 2012). While the little research that is currently available is certainly not enough, studies conducted so far have confirmed strong relations between the coleopterofauna of rivers and the various water bodies present on the floodplain, especially oxbows (Czachorowski et al, 1993;Mielewczyk, 2003;Biesiadka and Pakulnicka, 2004a;Przewoźny et al, 2006;Persson Vinnersten et al, 2009;Pakulnicka and Nowakowski, 2012;Costea et al, 2013). Similar data can be found also in relation to other water organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%